The First International Conference on Bio-resource and Stress Management: A Review - Das, Samares; Ramanjaneyulu, A. V.; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2023)
The First ever International Conference on Bio-resource and Stress Management was held during 6-9 February, 2013 at Science City, Kolkata, India under the chairmanship of Prof. R. K. Maiti, PhD, DSc and with the great leadership of co-chairman Prof. Humberto Gonzalez Rodriguez, PhD. The conference (www.bsmconf.in) was organized by Ratikanta Maiti Foundation (www.rkmf.org.in), Kolkata in collaboration with the technical partner, Central Research Institute for Jute and Allied Fibres (www.crijaf.org.in), Barrackpore, West Bengal, India and publishing partner, Puspa Publishing House, Kolkata